2002
DOI: 10.1093/brain/awf273
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor activity in spinal man: significance of afferent input from joint and load receptors

Abstract: The aim of this study was to differentiate the effects of body load and joint movements on the leg muscle activation pattern during assisted locomotion in spinal man. Stepping movements were induced by a driven gait orthosis (DGO) on a treadmill in patients with complete para-/tetraplegia and, for comparison, in healthy subjects. All subjects were unloaded by 70% of their body weight. EMG of upper and lower leg muscles and joint movements of the DGO of both legs were recorded. In the patients, normal stepping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
325
2
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(354 citation statements)
references
References 30 publications
21
325
2
6
Order By: Relevance
“…It was shown that treadmill exercises for patients with spinal cord injuries (SCI) improved their walking pattern (Barbeau and Rossignol (1994); Dietz and Harkema (2004); Edgerton et al (2004); Rossignol et al (2007); Wolpaw and Tennissen (2001)) which may be accounted for by the fact that CPGs can be trained to function independently from descending signals (Stein (2008)). Interestingly, Dietz et al (2002) showed that in a setting with 100% body unloading (thus limiting the role of stretch reflexes), patterned leg movements could be elicited in patients with para-and tetraplegia. Moreover, studies of disabled patients have shown that in the absence of sensory information, gross movement control is preserved, even if peripheral information is necessary for precise movement organization and control (see Jeannerod (1988) or Gandevia and Burke (1992)).…”
Section: Central Pattern Generatorsmentioning
confidence: 99%
“…It was shown that treadmill exercises for patients with spinal cord injuries (SCI) improved their walking pattern (Barbeau and Rossignol (1994); Dietz and Harkema (2004); Edgerton et al (2004); Rossignol et al (2007); Wolpaw and Tennissen (2001)) which may be accounted for by the fact that CPGs can be trained to function independently from descending signals (Stein (2008)). Interestingly, Dietz et al (2002) showed that in a setting with 100% body unloading (thus limiting the role of stretch reflexes), patterned leg movements could be elicited in patients with para-and tetraplegia. Moreover, studies of disabled patients have shown that in the absence of sensory information, gross movement control is preserved, even if peripheral information is necessary for precise movement organization and control (see Jeannerod (1988) or Gandevia and Burke (1992)).…”
Section: Central Pattern Generatorsmentioning
confidence: 99%
“…Analogously, afferents originating from the foot sole delay the initiation of swing and inhibit long latency flexion reflexes promoting stance (Duysens and Pearson, 1976;Conway et al, 1995). Although specific afferents or neuronal pathways have not been identified in humans, hip-mediated sensory signals affect the walking pattern of spinal injured people by enhancing the swing phase (Dietz et al, 1998(Dietz et al, ,2002, while input from the foot sole acting either in isolation or in combination with input from the hip affect reflexly mediated motor behavior (Knikou and Conway, 2001;Knikou, 2007a;Knikou et al, 2006b).…”
Section: Contribution Of Feedback From the Foot Sole And Hip To Spinamentioning
confidence: 99%
“…Evidence from studies conducted in lower vertebrates (Andersson and Grillner, 1983;Kriellaars et al, 1994;Hiebert et al, 1996;Lam and Pearson, 2001) suggest that this input accesses circuits responsible for walking contributing to phase transition and swing initiation. Blocking of the knee joint during human walking fails to alter the soleus H-reflex modulation pattern (Schneider et al, 2000), while pronounced hip extension enhances the swing phase during assisted walking in human SCI (Dietz et al, 1998(Dietz et al, ,2002. Further, sensory signals mediating static hip angle and sensation from the foot sole interact and induce a hip-dependent graded facilitation of the soleus H-reflex and tibialis anterior (TA) non-nociceptive flexion reflex in people with intact or injured spinal cord at rest (Knikou and Rymer, 2002;Knikou, 2005;Knikou et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…37 After complete SCI, it appears that local, segmental, proprioceptor motor circuits can be induced to generate patterned muscle activity, but not in a sustained manner. 36,38 In animals and humans, plasticity in the motor systems has been shown at different levels from the cortex to the target muscle. 39 Erroneous connections made after an injury persist for many years.…”
Section: Vertical Targetmentioning
confidence: 99%
“…There is also increasing evidence for degradation of neuronal function below the level of lesion in chronic, complete SCI. 38 The relevance of this degradation for a regeneration-inducing therapy needs to be evaluated. In addition, the prerequisites to facilitate the appropriate reconnection of regenerating tract fibres and to maintain neuronal function in the postacute stage have still to be established (see Vertical target 3).…”
Section: Horizontal Capabilitymentioning
confidence: 99%